China's lesser known migrants - Deng Quheng; Björn Gustafsson (Institute for the Study of Labor (IZA), 2006)
In China hukou (the household registration system) imposes barriers on permanent migration from rural to urban areas. Using large surveys for 2002, we find that permanent migrants number about 100 million persons and constitute approximately 20 percent of all urban residents. Receiving a long education, being a cadre or becoming an officer in the People's Liberation Army are important career paths towards urbanisation and permanent migrants are much better-off then their counterparts left behind in rural China. The probability of becoming a permanent migrant is positively related to parental education, belonging to the ethnic majority and the parent's membership in the Communist Party. At the destination, most permanent migrants are economically well-integrated. They have a higher probability to be working than their urban-born counterparts and those who receive a hukou before age 25 typically earn at least as much as their urban-born counterparts. The exceptions for this are those permanent migrants who receive a hukou after age 25 and people who received their hukou through informal routes.
Keywords: J61; O15; P36; 330; China; hukou; rural-to-urban migration